L1 AND L2 READING ATTITUDES AND THEIR CONTRIBUTION TOWARD READING HABIT - Sri Rejeki Murtiningsih (University of Kuningan, 2020)
The aims of the study are threefold. The first is to investigate the reading attitudes toward first language (L1) and second language (L2) in an English as a foreign language (EFL) context. The second aim is to find out the correlation between both variables. The last objective of the study is to find out the contribution of L2 reading attitude toward reading achievement. This study involved two sets of questionnaires adapted from Yamashita (2004) and Mikami (2016) and 177 freshmen, sophomore and junior English language education department students. The data revealed that means of reading attitude toward L1 and L2 are not significantly different with 2.60 and 2.65 respectively, and that reading attitude in L1 is strongly correlated with reading attitude in L2 (r = 0.637). An interesting finding of the present study pointed out that although students have positive attitude in L2, it does not automatically motivate them to spend their time reading. External factors such as teachers and specific reading programs both in L1 and L2 seem to play bigger roles in shaping students’ reading attitudes. Pedagogical implications are also discussedKeywords: Reading attitude in L1; reading attitude in L2; reading habit; external factors.